1988
DOI: 10.1007/bf01958941
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of phenylpropanoids in the rectal glands of males of the Oriental fruit fly,Dacus dorsalis

Abstract: Short Communicationsthey behave as if stimulated sexually by the flower labellum.Analyses of volatiles from O. litigiosa flowers 2o indicate the presence of citronellyl and farnesyl esters. These are biochemically closely related to geranyl esters and thus might be responsible for the attraction of male elaterid beetles to various Ophrys flowers.1 Financial assistance was donated by The Bank of Sweden Tercentenary Foundation and the Axel and Margaret Ax:son Jol~nson Foundation. We thank B. Baur for statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(100 citation statements)
references
References 3 publications
4
93
0
Order By: Relevance
“…Further, bioactive fractions from the haemolymph containing DMP and CF have been isolated (Hee and Tan, 2005), suggesting the involvement of putative pheromone binding proteins. Nishida (1988a) and found DMP and CF in the rectal gland of B. dorsalis males 6 d and as long as 20 d, respectively, after ingesting ME, indicating the capability for long-term retention of these chemicals. Importantly, ME metabolites have been detected in male volatile emissions (the pheromone "smoke" produced by Bactrocera males, Ohinata et al, 1982;Kuba and Sokei, 1988), DMP in the spray of B. dorsalis (Nishida et al, 1988a) and B. papayae and CF in the spray of B. carambolae .…”
Section: Fate Of Ingested Luresmentioning
confidence: 88%
See 3 more Smart Citations
“…Further, bioactive fractions from the haemolymph containing DMP and CF have been isolated (Hee and Tan, 2005), suggesting the involvement of putative pheromone binding proteins. Nishida (1988a) and found DMP and CF in the rectal gland of B. dorsalis males 6 d and as long as 20 d, respectively, after ingesting ME, indicating the capability for long-term retention of these chemicals. Importantly, ME metabolites have been detected in male volatile emissions (the pheromone "smoke" produced by Bactrocera males, Ohinata et al, 1982;Kuba and Sokei, 1988), DMP in the spray of B. dorsalis (Nishida et al, 1988a) and B. papayae and CF in the spray of B. carambolae .…”
Section: Fate Of Ingested Luresmentioning
confidence: 88%
“…Nishida (1988a) and found DMP and CF in the rectal gland of B. dorsalis males 6 d and as long as 20 d, respectively, after ingesting ME, indicating the capability for long-term retention of these chemicals. Importantly, ME metabolites have been detected in male volatile emissions (the pheromone "smoke" produced by Bactrocera males, Ohinata et al, 1982;Kuba and Sokei, 1988), DMP in the spray of B. dorsalis (Nishida et al, 1988a) and B. papayae and CF in the spray of B. carambolae . In addition, females have been shown to be attracted to the ME derivatives presented either singly or in a blend (Tan and Nishida, 1996;Nishida et al, 1997;Hee and Tan, 1998;.…”
Section: Fate Of Ingested Luresmentioning
confidence: 88%
See 2 more Smart Citations
“…After feeding on an attractant source, males of Bactrocera species incorporate the chemicals selectively in their rectal glands, which are presumed to function as a reservoir of sex pheromone to attract females, as demonstrated in methyl eugenol-B. dorsalis association (Nishida et al, 1988;Shelly and Dewire, 1994;Hee and Tan, 1998;Tan and Nishida, 1998). It was shown that sexually mature males of B. latifrons that fed on a series of 3-oxygenated a-ionone/a-ionol analogs selectively incorporate and partially biotransform the compounds in a specific ratio and store the metabolites in the rectal gland (Nishida et al, 2009), suggesting a possible pheromonal role of the components in their life cycle.…”
Section: Introductionmentioning
confidence: 99%